Isolation of aerobic cultivable cellulolytic bacteria from different regions of the gastrointestinal tract of giant land snail Achatina fulica - Pinheiro, Guilherme L.; Correa, Raquel; Soares, Raquel; Cardoso, Alexander; Chaia, Catia; Clementino, Mayssa M.; Garcia, Eloi; De Souza, Wanderley; Frases, Susana (Frontiers in Microbiology, 2015)
The enzymatic hydrolysis of cellulose by cellulases is one of the major limiting steps in the conversion of lignocellulosic biomass to yield bioethanol. To overcome this hindrance, significant efforts are underway to identify novel cellulases. The snail Achatina fulica is a gastropod with high cellulolytic activity, mainly due to the abundance of glycoside hydrolases produced by both the animal and its resident microbiota. In this study, we partially assessed the cellulolytic bacterial diversity inside the gastrointestinal tract of A. fulica by culture-dependent methods and evaluated the hydrolytic repertoire of the isolates. Forty bacterial isolates were recovered from distinct segments of the snail gut and identified to the genus level by 16S rRNA gene sequence analysis. Additional phenotypic characterization was performed using biochemical tests provided by the Vitek2 identification system. The overall enzymatic repertoire of the isolated strains was investigated by enzymatic plate assays, containing the following substrates: powdered sugarcane bagasse, carboxymethylcellulose (CMC), p-nitrophenyl-b-D-glucopyranoside (pNPG), p-nitrophenyl-b-D-cellobioside (pNPC), 4-methylumbelliferyl-b-D-glucopyranoside (MUG), 4-methylumbelliferyl-b-D-cellobioside (MUC) and 4-methylumbelliferyl-b-D-xylopyranoside (MUX). Our results indicate that the snail Achatina fulica is an attractive source of cultivable bacteria that showed to be valuable resources for the production of different types of biomass-degrading enzymes.